The Implementation of HIV Self-Testing in Resource-Limited Settings Where the HIV Disease Burden is High - Pachamuthu Balakrishnan; A. S. Smiline Girija; Saravanan Shanmugam; Iyanar Kannan; Ramachandran Vignesh; Esaki M. Shankar; Sree T. Sucharitha (Frontiers Media S.A., 2023)
In resource-limited settings, there is growing evidence that HIV testing is lacking among high-risk key populations such as men having sex with men, injection drug users, and transgenders largely due to stigma, discrimination, and lack of confidentiality. Findings from recent studies among high-risk key populations and the general population from various regions including resource-limited settings support the need for wider accessibility of HIV self-testing (HIV-ST) to reach those who may not otherwise have access to testing. Therefore, HIV-ST has untapped potential as a strategy to improve access to HIV testing and to increase testing frequency among key high-risk populations and their partners. Though HIV-ST has emerged as a safe, acceptable, and effective way to reach people, there are several roadblocks to implementing the HIV-ST policy, and fast-track policy implementation needs to be necessitated with newer or modified strategic plans.